Study of Factors Affecting the Profitability and Firm Value of LQ45 - Ramadhani Annisa Zein; Muhammad Ali; Andi Ratna sari Dewi (Hasanuddin Journal of Applied Business and Entrepreneurship, 2020)
The value of the company is an investor perception to the company, which is often associated with the stock price. The higher the value, the higher the company’s shareholder wealth. One proxy of the firm value is Price to Book Value (PBV). PBV is the ratio of stock price to book value of the company. The purpose of this research was to examine the significance of the effect of capital structure (DER), brand value, inflation and exchange rate partially on profitability (ROE) and firm value (PBV), both direct, indirect and the total effect. The sample used was companies in the LQ45 index with an observation period of 2014 to 2018 with a total of 20 companies collected through purposive sampling. Testing the research hypothesis using path analysis techniques. Data were analyzed using IBM SPSS Statistics 23 software. This result showed that: (1) Brand value has a positive and significant effect on profitability, while inflation and exchange rate have a negative and significant effect on profitability. (2) Brand value has a positive and significant effect on firm value, while capital structure has a negative and significant effect on firm value. (3) Profitability is proven to have a positive and significant effect on firm value. (4) Profitability can be used as an intervening variable on each independent variable because the value of the indirect effect is greater than the direct effect on the firm's value.